Analisis Tingkat Keuntungan Usaha Pembesaran Ikan Lele (Clarias Sp.) Dengan Teknik Bioflok Di Kabupaten Oku Timur - Yudhi Zuriah (Sekolah Tinggi Ilmu Pertanian (STIPER) Belitang, 2019)
The objectives of this study were to: 1) determine the amount of income in the business of raising catfish using the biofloc technique in East OKU Regency, 2) to analyze the profit level of the catfish rearing business using the biofloc technique in East OKU Regency. The results showed that the average income of catfish rearing using biofloc technique was Rp. 3,702,121 / pp. Catfish enlargement business using biofloc technique provides a level of profit with an average R / C value of 1.85 and a B / C value of 0.85 and an average BEP of IDR 8,697 / kg and a product BEP of 20.31 kg. / pp.